Analisis Pengelolaan Obat di Puskesmas Margamulya Kecamatan Bekasi Utara Tahun 2021 - Rukmana, Taufiq Indra; Nusaiba, Putri; Sitepu, Eme Stepani (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Primary Health Center still has problem in drug management, especially in drug availability, storage, and drug inventory control. This study aims to analyze whether drug management at the Margamulya Primary Health Center in 2021 met the standard indicators of drug management. This study used observational descriptive research methods. Data collection was carried out using secondary data tracing (retrospective), direct observation (concurrent), and interviews. The collected data were then analyzed with drug management indicators consisting of 26 indicators. The analysis results showed that drug management at the Margamulya Primary Health Center met 9 indicators, but did not meet 15 indicators, when compared to standards. In addition, 2 indicators could not be analyzed because of lack of data. Thus, it is necessary to review aspects of drug inventory control, to increase the number, soft skills and knowledge of pharmacist in pharmaceutical services, and to implement management information system in the Primary Health Center.